2021
DOI: 10.21037/apm-21-3533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different pedicle screw fixation schemes in the treatment of neurosurgical spinal fractures: systematic review and meta-analysis

Abstract: Background: Thoracolumbar fractures have the characteristics of acute onset, rapid change, and severe trauma. The best way to treat thoracolumbar fractures is through fracture reduction surgery. The surgical methods include percutaneous pedicle screw, posterior percutaneous pedicle screw internal fixation, and open pedicle screw internal fixation.Methods: We searched the PubMed, Embase, and Medline English database from April 1991 to April 2021, and the keywords included "percutaneous tablet screen", "posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Patients' vertebral fractures have limited mobility and severe pain, which affects their life functions and is treated mainly by surgical means [ 13 ]. The application of traditional surgical treatment can effectively correct and reset the fracture end, but it has more complications and can cause significant damage to the patient with high bleeding, which affects the patient's postoperative recovery [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients' vertebral fractures have limited mobility and severe pain, which affects their life functions and is treated mainly by surgical means [ 13 ]. The application of traditional surgical treatment can effectively correct and reset the fracture end, but it has more complications and can cause significant damage to the patient with high bleeding, which affects the patient's postoperative recovery [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…PS fixation is the method of choice for surgical implantation in spine‐related diseases. 2 However, it also has some shortcomings: screw placement often requires the dissection of more muscles; visual field is poor, especially in the lower lumbar spine or sacrum; tendency to invade the surrounding facet joints; and the nerve is prone to injury. 3 , 4 Moreover, PS loosens easily in older patients with osteoporosis because the screw insertion channel is encased in the cancellous bone.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional pedicle screw (PS) fixation has been used in clinical practice for several years with excellent correction, spinal stability, and fusion results. PS fixation is the method of choice for surgical implantation in spine‐related diseases 2 . However, it also has some shortcomings: screw placement often requires the dissection of more muscles; visual field is poor, especially in the lower lumbar spine or sacrum; tendency to invade the surrounding facet joints; and the nerve is prone to injury 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] While certain types of fractures still pose a treatment controversy, treatment of TLF often involves the use of posterior segment fixation. [5,6] In the past, posterior internal fixation (PIF) was typically performed using a 4-screw configuration in a short segment (SS), with 2 pedicle screws inserted into the upper and lower adjacent vertebrae of the fractured vertebral body. [7] Studies have demonstrated that the SS technique may not be adequate for adequately realigning the fractured vertebral body and resolving kyphosis.…”
Section: Introductionmentioning
confidence: 99%